Modifier-numeral word order in the English NP: An FDG analysis - Keizer, Evelien (Open Linguistics, 2022)
It is generally accepted that the order of elements within the English noun phrase is relatively fixed, and that, in the prefield, determiners (primary and secondary) precede modifiers. This article is concerned with a group of noun phrases exhibiting non-canonical word order, namely those cases in which a modifier precedes a numeral, such as , , and . Using corpus data from the , it is shown that such noun phrases are far more heterogeneous (in terms of the kind of noun, the scope and type of the modifier, the form and number of the determiner, and subject-verb agreement) than assumed in previous studies. It is argued that the variation observed in the data can only be accounted for if different subtypes of such NPs are distinguished, each characterized by its own combination of functional and formal properties. Finally, it is demonstrated how Functional Discourse Grammar, with its function-to-form approach and its different levels and layers of representation, is particularly well-suited to capture the main features of the construction as a whole, as well as the more specific semantic and syntactic properties of each of the subtypes.